Contour Error Control for a Hybrid Robot Equipped with Grating Sensors - Xianlei Shan; Tianyu Zou; Haitao Liu; Yu Deng; Juliang Xiao (Machines)
To mitigate the detrimental effects of joint elasticity and transmission errors on contour accuracy and to improve the multi-axis motion performance of hybrid robots, this study investigates contour error modeling and control by leveraging additional grating sensors for real-time measurements. Accounting for the inherent pose coupling characteristics of hybrid robots, a novel contour error modeling method is proposed that employs six-dimensional exponential coordinates for error description and incorporates an efficient search algorithm for foot point determination. Building upon an existing grating sensor feedback control framework, a proportional contour controller is developed. Experimental validation on the TriMule-200 hybrid robot demonstrates an enhancement in end-effector contour accuracy.